Positive Coping and Resilience: Questions and Conclusions Drawn from a Longitudinal Study - Berszán, Lídia (European Journal of Mental Health, 2017)
In 2002-2004, during a research about families taking care of disabled children or adults, we created the criteria of coping successfully. Interpreting through this filter the resulting data and the responses a coping profile has outlined. Ten years later, we repeated the survey and found that in the interpretation of the data, the coping criteria from the first research was not sustainable. To better understand this phenomenon, we performed in-depth interviews and we added a CHIP (Coping Health Inventory For Parents) questionnaire that provides insight to coping behaviours used by parents. The results we obtained further highlighted our suspicion that the factor of successful coping from the first period of facing disabilities significantly changed through the years. This phenomenon can be interpreted not only in terms of the life of individual families, but also shows the overlaps and differences between the meanings of the terms ‘coping- and ‘resilience-, and the professional challenge brought by the supported resilience in the ‘overseeing- of these families.